Analisis Manajemen Risiko Pada UMKM “Bantal dan Kasur” Baleendah Kabupaten Bandung - Halim, Nizar Husni (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Micro, Small and Medium Enterprises (MSMEs) in the pillow and mattress production sector have great market potential, but are faced with various risks that can threaten business sustainability. This study aims to identify, analyze, and develop risk mitigation strategies faced by pillow and mattress MSMEs. The method used is risk analysis through the stages of identification, assessment, and formulation of mitigation strategies for major risks. The risks identified include delays in raw materials, price fluctuations, damage to production equipment, product quality, and customer satisfaction. The results of the study indicate that appropriate mitigation strategies, such as supplier diversification, maintenance of production equipment, and implementation of strict product quality control, can reduce the negative impact of the risks faced. The implementation of this risk management is expected to increase the competitiveness and resilience of MSMEs in the pillow and mattress sector